136 Reviewing the change in management of emergency renal colic services and surgical intervention impacted by COVID-19. (16th November 2020) - Woo, Caroline; Quraishi, Mohammed Kamil; Gabriel, Joseph; Mackie, Simon; Watson, Graham
Abstract : Background and Aim: COVID-19 has resulted in changes to how the healthcare system in the United Kingdom delivered its emergency care, including renal colic and its management. Our stone team amended its services in order to reduce stone related morbidity and preventable hospital admissions. We aim to review similar time periods in 2019 and 2020 to see how this has changed. Methods: A retrospective review of all presentations of acute renal colic with CT confirmed stones were carried out for the months of April to May, 2019 and 2020. Demographics, clinical features and stone characteristics and treatment were noted. Results: Seventy nine percent of the 38 patients who present in 2019 had ureteric stones, compared to 85% of the 40 patients in 2020. Distal stones made up 53% in 2019, compared to 56% in 2020. Less patients were noted to be febrile in 2020(13%vs35%). There was an increase in conservative management in 2020 (25% vs 21%). Emergency treatment (stent/nephrostomy) with secondary intervention (Ureterorenoscopy(URS)/Percutaneous Nephrolithotomy (PCNL)) was markedly reduced in 2020(12.5% vs 42%).More patients were also treated with primary interventions (URS/PCNL) within 48 hours (43% in 2020 vs 26%) and 7 days (13% vs 8%). Conclusion: More patients were treated with conservative treatments and early primary interventions. This was done in order to combat unnecessary hospital admissions and stays, as well as surgeries and anaesthesia, whilst minimising stone and stent complications. An improved adherence to GIRFT guideless was also noted, providing better patient care and outcome, whilst reducing unnecessary procedures.